Metabolites of intestinal fora can be used as diagnostic and progressive markers for mild cognitive impairment - Lu, Liquan; Qin, Lei; Zhao, Xiaohui; Liu, Zanhua; Qiu, Xiaoting; Yang, Shuo; Song, Haihan; Yang, Juan (Frontiers in Cellular and Infection Microbiology, 2024)
The aim of the work was to analyze the metabolites of the intestinal microbiota from the patients with mild cognitive impairment (MCI) due to Alzheimer's disease and progressive MCI due to Alzheimer's disease.Two cohorts were established. The first one included 87 subjects with 30 healthy controls (NC), 22 patients with MCI due to Alzheimer's disease, and 35 patients with Alzheimer's disease (AD). The second cohort included 87 patients with MCI due to Alzheimer's disease, who were followed up for 2 years, and finally were divided into progressive MCI due to Alzheimer's disease group (P-G) and unprogressive MCI due to Alzheimer's disease group (U-G) according their cognitive levels. Fecal samples were collected to all patients at the baseline time point. Differential metabolites were subjected to pathway analysis by MetaboAnalyst.Results: In the first cohort, we found 21 different metabolites among the three groups (AD and MCI and NC). In the second cohort, we identified 19 differential metabolites between P-G and U-G groups. By machine learning analysis, we found that 7 characteristic metabolites (Erythrodiol, alpha-Curcumene, Synephrine, o-Hydroxylaminobenzoate, 3-Amino-4-hydroxybenzoic acid, 2-Deoxystreptamine and 9(S)-HPOT) were of characteristic significance for the diagnosis of MCI due to Alzheimer's disease, and 6 metabolites (Indolelactate, Indole-3-acetaldehyde, L-Proline, Perillyl, Mesaconate and Sphingosine) were the characteristic metabolites of early warning for the progression of MCI due to Alzheimer's disease. D-Glucuronic acid was negatively correlated with APOE4. Perillyl alcohol was negatively correlated with all of the five biomarkers (P-tau181and NF-light and Aβ1-42 and Aβ1-40 and GFAP), but Indoleacetaldehyde was positively correlated with three biomarkers (P-tau181 and Aβ1-42 and GFAP). Three characteristic metabolites (3-Amino-4-hydroxybenzoate and 2-Deoxystreptamine and p-Synephrine) were positively correlated with Aβ1-42. 2-Deoxystreptamine and 9(S)-HPOT and Indoleacetaldehyde were positively correlated with GFAP. L-Proline and Indoleacetaldehyde were positively correlated with NF-light.Specific metabolites of intestinal fora can be used as diagnostic and progressive markers for mild cognitive impairment.